Evaluating the importance of mature trees for birds in urban landscapes - Yong, Cheryl Kai Lin (Nanyang Technological University, 2024)
Urban green spaces can act as strongholds for biodiversity in the face of rapid urban expansion into natural habitats. Simultaneously, they provide an interface for human-nature interactions to improve the well-being of urban dwellers. Being more visible than other taxonomic groups, birds can have a greater impact on the perception of diversity in the area and hence improve people’s mental health. Current measures to manage urban green spaces for birds mainly focus on habitat enhancement, including using feeders, nest boxes and plant choice. However, pre-development planning prior to land clearance and urban design is often overlooked, particularly with respect to mature trees. Mature trees provide a disproportionately large supply of food resources, suitable branches for perching and hollows for nesting. These features may take centuries to form and are difficult to recover once the trees are cleared. By conducting bird and vegetation surveys across 36 sites in urban residential areas, my study aimed to evaluate the effectiveness of retaining mature trees in maximising avian diversity. I found that the number of mature trees in a site and in a 200m buffer, as well as site area, were the most important variables in determining the overall richness and abundance of birds and richness and abundance of hollow-dependent birds at the site level. Such findings can be a foundation for establishing design and management guidelines for urban developers, where both individual and clusters of mature trees can be retained and planned around to form urban green spaces in new suburbs.